Infrared heat reflective thermoplastic polyolefin waterproofing membrane and preparation method thereof

By adding far-infrared ceramic powder, rutile titanium dioxide and other components to the thermoplastic polyolefin waterproof coil, a heat-insulating cross-linking network structure is formed, which solves the problems of thermal aging and combustion ease of waterproof coil under high temperature conditions, and achieves excellent heat-resistant aging and flame retardant properties.

CN119431918BActive Publication Date: 2025-04-25ANHUI DAYU WATERPROOF TECH DEV CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510037884.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-25
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

Existing thermoplastic polyolefin waterproof coils are prone to thermal aging under high temperature conditions, resulting in a decrease in performance, and also have ease of combustion, which affects its widespread application.

Method used

The preparation method of infrared heat-reflective thermoplastic polyolefin waterproof coil is adopted, and the heat-insulating cross-linking network structure is formed by adding components such as far-infrared ceramic powder, rutile titanium dioxide, functional titanium dioxide IR-1000 and branched structures of hexachlorocyclotriphosphazene hindered phenol to form a heat-insulating cross-linking network structure to improve the heat-resistant aging and flame-retardant properties of the water-resistant coil.

Benefits of technology

It significantly improves the heat-resistant aging and flame retardant properties of the waterproof coil, meets the B2 grade flame retardant requirements of the new regulations on thermoplastic polyolefin waterproof coils, and improves its mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431918B_ABST
    Figure CN119431918B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of waterproofing coiled materials, and discloses an infrared heat reflecting thermoplastic polyolefin waterproofing coiled material and a preparation method thereof. The invention uses hexachlorocyclotriphosphazene, aminopropyltriethoxysilane, formaldehyde and the like as raw materials, and undergoes a series of reactions to obtain hexachlorocyclotriphosphazene silane, which is condensed with nano far-infrared ceramic powder and rutile titanium dioxide to obtain modified nano far-infrared ceramic powder and modified rutile titanium dioxide, and uses intermediate product 1 to react with β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl chloride to obtain hexachlorocyclotriphosphazene hindered phenol. Finally, polyolefin elastomer, functional titanium dioxide IR-1000, modified nano far-infrared ceramic powder and the like are uniformly mixed, melt-plasticized, cooled and shaped to obtain infrared heat reflecting thermoplastic polyolefin waterproofing coiled material. The waterproofing coiled material prepared by the invention has been confirmed to have excellent flame retardant properties, heat aging resistance and mechanical properties through experiments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waterproof coiled materials, in particular to an infrared heat reflective thermoplastic polyolefin waterproof coiled material and a preparation method thereof. Background Art

[0002] With the increasing demand for buildings, waterproof membranes, as an important waterproof material, are widely used in waterproof projects such as building roofs and basements. However, during their application, they will be affected by various external factors, among which thermal aging is one of the factors affecting the performance of waterproof membranes. Thermal aging refers to the phenomenon that the performance of materials deteriorates after being exposed to high temperature conditions for a long time. Therefore, the study of infrared heat reflective thermoplastic polyolefin waterproof membranes has practical significance for improving the heat aging resistance of waterproof membranes.

[0003] Thermoplastic polyolefin (TPO) waterproof membrane is a new type of polymer waterproof membrane, mainly composed of polyolefin, rubber and various additives. However, TPO waterproof membrane is very easy to burn. The fire caused by it may have serious life and economic impacts on social public safety and life, which seriously restricts the widespread use of TPO waterproof membrane. Therefore, it is necessary to prepare a thermoplastic polyolefin waterproof membrane with flame retardant effect.

[0004] For example, the patent with application publication number CN 117659882 A discloses a highly flame-retardant and long-life thermoplastic polyolefin waterproof membrane and a preparation method thereof. The invention proposes a highly flame-retardant and long-life thermoplastic polyolefin waterproof membrane and a preparation method thereof, including a thermoplastic polyolefin waterproof base layer composed of polypropylene, light stabilizer, inorganic flame retardant, etc., with good flame retardant and mechanical properties, but does not improve the heat aging resistance of the waterproof membrane. Summary of the invention

[0005] The purpose of the present invention is to overcome one or more deficiencies in the prior art and to provide an infrared heat reflective thermoplastic polyolefin waterproof membrane. The waterproof membrane prepared by the method has excellent flame retardant properties, heat aging resistance and mechanical properties.

[0006] In order to achieve the above object, a technical solution adopted by the present invention is:

[0007] An infrared heat reflective thermoplastic polyolefin waterproofing coiled material, characterized in that the waterproofing coiled material is composed of the following components in parts by weight: 100 parts by weight of thermoplastic polyolefin, 20-50 parts of a first polypropylene, 10-30 parts of a second polypropylene, 5-20 parts of a hydrogenated styrene-isoprene copolymer, 60-90 parts of magnesium hydroxide, 10-30 parts of functional titanium dioxide IR-1000, 10-30 parts of modified nano far-infrared ceramic powder, 10-30 parts of modified rutile titanium dioxide, 2-5 parts of hexachlorocyclotriphosphazene hindered phenol, 0.1-2 parts of hindered amine light stabilizer C2020, and 0.1-1 parts of anti-copper agent MD1024;

[0008] The preparation method of the infrared heat reflective thermoplastic polyolefin waterproof coiled material is as follows:

[0009] (1) Under a nitrogen atmosphere, hexachlorocyclotriphosphazene and 4,5-diaminobenzene-1,2-diphenol are added to a flask containing a toluene solvent, stirred and dispersed, and triethylamine is added thereto, stirred and mixed evenly, and the temperature is controlled to be 100-110° C. and reacted for 5-8 hours. After the reaction is completed, the reaction is cooled to room temperature, filtered, washed, and dried to obtain an intermediate product 1. Hexachlorocyclotriphosphazene and 4,5-diaminobenzene-1,2-diphenol are used to undergo a cyclization reaction under the catalysis of triethylamine to obtain an intermediate product 1. The reaction route is as follows:

[0010] ;

[0011] (2) Calcium hydride is added to chloroform solvent, stirred at room temperature for 20-30 minutes, and then aminopropyl triethoxysilane and formaldehyde are added thereto, stirred and reacted at 50-55°C for 40-60 minutes, and intermediate product 1 is added thereto, and the temperature is raised to 60-65°C. Under nitrogen protection, the reaction is carried out for 5-7 hours. After the reaction is completed, the mixture is filtered, rotary evaporated, washed, and dried to obtain hexachlorocyclotriphosphazene silane. The phenolic hydroxyl group in the intermediate product 1 is reacted with formaldehyde and aminopropyl triethoxysilane through Manniene reaction to obtain hexachlorocyclotriphosphazene silane. The reaction route is as follows:

[0012] ;

[0013] (3) adding hexachlorocyclotriphosphazene silane to a 75% by mass ethanol aqueous solution, stirring and dispersing, and then adding dry nano far-infrared ceramic powder thereto, ultrasonically dispersing for 10-20 minutes, heating to 60-70° C., and continuing the reaction for 20-40 minutes. After the reaction is completed, drying and grinding are performed to obtain modified nano far-infrared ceramic powder;

[0014] (4) adding rutile titanium dioxide to deionized water, adjusting the pH to 6 with 10% by mass hydrochloric acid, adding hexachlorocyclotriphosphazene silane, stirring and dispersing for 20-30 minutes, heating to 75-85° C., reacting for 1-2 hours, and after the reaction is completed, centrifuging, washing with deionized water, drying, and grinding to obtain modified rutile titanium dioxide;

[0015] (5) Add thermoplastic polyolefin, the first polypropylene, the second polypropylene, hydrogenated styrene-isoprene copolymer, magnesium hydroxide, anti-copper agent, functional titanium dioxide IR-1000, modified nano far-infrared ceramic powder, modified rutile titanium dioxide, hexachlorocyclotriphosphazene hindered phenol, and hindered amine light stabilizer into a high-speed mixer, mix at a speed of 100 r / min for 5-10 minutes, then add it into a twin-screw extruder, melt plasticize, and cool and shape it through a three-roll calender to obtain an infrared heat reflective thermoplastic polyolefin waterproof membrane.

[0016] Preferably, in (1), the mass ratio of hexachlorocyclotriphosphazene, 4,5-diaminobenzene-1,2-diphenol and triethylamine is 1:0.4-0.6:1.8-2.

[0017] Preferably, in (2), the mass ratio of calcium hydride, aminopropyltriethoxysilane, formaldehyde and intermediate product 1 is 0.7-1:2.4-2.8:0.6-1:1.

[0018] Preferably, in (3), the mass of hexachlorocyclotriphosphazene silane is 10-20% of the mass of the nano far-infrared ceramic powder.

[0019] Preferably, in (4), the mass of hexachlorocyclotriphosphazene silane is 10-20% of the mass of rutile titanium dioxide.

[0020] Preferably, in (5), the temperatures of the screw zones are 200°C, 205°C, 210°C, 215°C, 218°C, and 220°C, the die head temperature is 220°C, and the screw speed is 200-500 r / min.

[0021] Preferably, in (5), the preparation method of hexachlorocyclotriphosphazene hindered phenol is:

[0022] Under nitrogen atmosphere, the intermediate product 1 and triethylamine are added to chloroform, stirred and dispersed, and β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl chloride is added thereto at 10-20°C, the temperature is raised to 55-60°C, and the reaction is carried out for 10-16 hours. After the reaction is completed, the mixture is rotary evaporated, washed with saturated brine, and dried to obtain hexachlorocyclotriphosphazene hindered phenol. The phenolic hydroxyl group in the intermediate product 1 is subjected to esterification reaction with β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl chloride under the catalysis of triethylamine to obtain hexachlorocyclotriphosphazene hindered phenol, and the reaction formula is:

[0023] .

[0024] Further preferably, the mass ratio of the intermediate product 1, triethylamine and β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl chloride is 1:1.2-1.6:3.2-4.

[0025] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0026] (1) The functional titanium dioxide IR-1000 used in the present invention is a sulfuric acid process rutile titanium dioxide with a particle size greater than 800nm, and has a 5-8% by mass aluminum oxide film on its surface, which is a dense coating layer with strong weather resistance. The far-infrared ceramic powder and rutile titanium dioxide used in the present invention have a strong interaction with the molecular chain of the matrix material after organic treatment, and can be evenly dispersed in the matrix material. The far-infrared ceramic powder, rutile titanium dioxide, and functional titanium dioxide IR-1000 act as rigid support points and physical cross-linking points in the matrix material, which can not only withstand and transmit the force, so that the mechanical properties of the thermoplastic polyolefin waterproof membrane are improved, but also can reduce the fluidity of the thermoplastic polyolefin molecular chain, reduce the possibility of degradation reaction, and improve the heat aging resistance of the waterproof membrane. In addition, the hexachlorocyclotriphosphazene silane and hexachlorocyclotriphosphazene hindered phenol prepared by the present invention contain a large number of branched structures, which can be cross-linked and entangled with thermoplastic polyolefin molecular chains to form a larger cross-linked network structure, further improving the mechanical properties of the waterproof membrane.

[0027] (2) The far-infrared ceramic powder used in the present invention has a high infrared emissivity, and can radiate the absorbed sunlight into the atmosphere in the form of thermal radiation, thereby increasing the heat insulation effect, reducing the influence of heat on the waterproofing membrane, and improving the heat aging resistance of the waterproofing membrane. The rutile titanium dioxide and functional titanium dioxide IR-1000 used have a high refractive index, which can reflect most of the energy, effectively reduce convective heat transfer and radiation heat transfer, further reduce the influence of heat on the waterproofing membrane, and further improve the heat aging resistance of the waterproofing membrane. The far-infrared ceramic powder, rutile titanium dioxide, and functional titanium dioxide IR-1000 are evenly dispersed in the waterproofing membrane to form a heat-insulating cross-linked network structure. The three assist each other in jointly improving the heat aging resistance of the waterproofing membrane. In addition, the waterproof membrane prepared by the present invention also has a benzoxazine structure and a hindered phenol structure in the molecular chain. When the benzoxazine structure is subjected to heat, it can open the ring and cross-link to form a cross-linked network structure, thereby improving the heat aging resistance of the waterproof membrane. When the molecular chain of the waterproof membrane is affected by high temperature and free radicals are generated, the hindered phenol structure can destroy the free radical self-oxidation chain reaction, and cooperate with the hindered amine light stabilizer to further improve the heat aging resistance of the waterproof membrane.

[0028] (3) The waterproof membrane prepared by the present invention also has flame-retardant phosphorus, nitrogen and silicon elements, which form a phosphorus-nitrogen-silicon synergistic flame retardant system. The far-infrared ceramic powder, rutile titanium dioxide, functional titanium dioxide IR-1000 and magnesium hydroxide contained therein as inorganic materials can form an organic-inorganic synergistic flame retardant system with the organic phosphorus-nitrogen-silicon synergistic flame retardant system. The waterproof membrane prepared by the present invention has been confirmed by experiments to meet the B2 grade flame retardancy required by the new regulations for thermoplastic polyolefin waterproof membranes. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is the structural diagram of hexachlorocyclotriphosphazene silane;

[0030] Figure 2 This is the carbon NMR spectrum of hexachlorocyclotriphosphazene silane. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Preparation method of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl chloride: under nitrogen atmosphere, add 0.1 mol of methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate to ethanol solvent, control the temperature to 60-70°C, add 30% by mass sodium hydroxide solution thereto, react for 5 hours, adjust pH to 3 with 10% by mass hydrochloric acid after the reaction, filter, wash with deionized water, dry, dissolve in chloroform solvent, add 0.2 mol of dichlorothionyl thereto, react for 5 hours, distill under reduced pressure after the reaction, and dry to obtain β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl chloride. Embodiment 1

[0033] (1) Under a nitrogen atmosphere, 3.5 g of hexachlorocyclotriphosphazene and 1.4 g of 4,5-diaminobenzene-1,2-diphenol were added to a flask containing toluene solvent and stirred to disperse. Then, 7 g of triethylamine was added thereto and stirred to mix evenly. The temperature was controlled at 105°C and the reaction was carried out for 8 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed and dried to obtain an intermediate product 1.

[0034] (2) Under a nitrogen atmosphere, 5.5 g of the intermediate product 1 and 7 g of triethylamine were added to chloroform and stirred for dispersion. Then, 18 g of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl chloride was added thereto at 15°C. The temperature was raised to 60°C and the reaction was carried out for 14 h. After the reaction was completed, the mixture was rotary evaporated, washed with saturated brine, and dried to obtain hexachlorocyclotriphosphazene hindered phenol.

[0035] (3) Add 4 g of calcium hydride to chloroform solvent and stir at room temperature for 30 min. Then add 15 g of aminopropyltriethoxysilane and 4 g of formaldehyde and stir at 55 °C for 60 min. Then add 5.5 g of intermediate 1 and heat to 60 °C. Under nitrogen protection, react for 6 h. After the reaction, filter, rotary evaporate, wash and dry to obtain hexachlorocyclotriphosphazene silane.

[0036] (4) Add 0.4 g of hexachlorocyclotriphosphazene silane to a 75% by mass ethanol aqueous solution, stir and disperse, then add 20 g of dry nano far-infrared ceramic powder, ultrasonically disperse for 15 min, heat to 60 ° C, and continue to react for 40 min. After the reaction is completed, dry and grind to obtain modified nano far-infrared ceramic powder.

[0037] (5) 20 g of rutile titanium dioxide was added to deionized water, and the pH value was adjusted to 6 using 10% by mass hydrochloric acid. 0.2 g of hexachlorocyclotriphosphazene silane was added thereto, and the mixture was stirred and dispersed for 30 min. The mixture was heated to 80 °C and reacted for 2 h. After the reaction was completed, the mixture was centrifuged, washed with deionized water, dried, and ground to obtain modified rutile titanium dioxide.

[0038] (6) 100 g of thermoplastic polyolefin CA10A, 20 g of first polypropylene NS06, 40 g of second polypropylene K8003, 40 g of hydrogenated styrene-isoprene copolymer 4052, 70 g of magnesium hydroxide, 0.1 g of anti-copper agent MD1024, 10 g of functional titanium dioxide IR-1000, 10 g of modified nano far-infrared ceramic powder, 10 g of modified rutile titanium dioxide, 2 g of hexachlorocyclotriphosphazene hindered phenol, 0.1 g of hindered Amine light stabilizer C2020 was added to a high-speed mixer and mixed for 10 minutes at a speed of 100 r / min. Then it was added to a twin-screw extruder. The temperatures of each screw zone were 200°C, 205°C, 210°C, 215°C, 218°C, and 220°C. The head temperature was 220°C, the screw speed was 500 r / min, and it was melt-plasticized. After cooling and shaping by a three-roll calender, an infrared heat reflective thermoplastic polyolefin waterproof membrane was obtained. Embodiment 2

[0039] (1) Under a nitrogen atmosphere, 3.5 g of hexachlorocyclotriphosphazene and 1.5 g of 4,5-diaminobenzene-1,2-diphenol were added to a flask containing toluene solvent and stirred to disperse. Then, 6.3 g of triethylamine was added thereto and stirred to mix evenly. The temperature was controlled at 110°C and the reaction was carried out for 5 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed and dried to obtain an intermediate product 1.

[0040] (2) Under a nitrogen atmosphere, 5.5 g of the intermediate product 1 and 7.7 g of triethylamine were added to chloroform and stirred for dispersion. At 20° C., 20 g of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl chloride was added thereto. The temperature was raised to 60° C. and the reaction was carried out for 14 h. After the reaction was completed, the mixture was rotary evaporated, washed with saturated brine, and dried to obtain hexachlorocyclotriphosphazene hindered phenol.

[0041] (3) Add 5.5 g of calcium hydride to chloroform solvent, stir at room temperature for 30 min, then add 14 g of aminopropyltriethoxysilane and 5.5 g of formaldehyde, stir and react at 50 °C for 50 min, add 5.5 g of intermediate 1, raise the temperature to 65 °C, react for 7 h under nitrogen protection, filter, rotary evaporate, wash and dry to obtain hexachlorocyclotriphosphazene silane.

[0042] (4) Add 0.3 g of hexachlorocyclotriphosphazene silane to a 75% by mass ethanol aqueous solution, stir and disperse, then add 20 g of dry nano far-infrared ceramic powder, ultrasonically disperse for 10 min, heat to 70 ° C, and continue to react for 20 min. After the reaction is completed, dry and grind to obtain modified nano far-infrared ceramic powder.

[0043] (5) Add 20 g of rutile titanium dioxide to deionized water, adjust the pH to 6 with 10% by mass hydrochloric acid, add 0.4 g of hexachlorocyclotriphosphazene silane, stir and disperse for 25 min, heat to 85 °C, react for 1 h, and after the reaction is completed, centrifuge, wash with deionized water, dry, and grind to obtain modified rutile titanium dioxide.

[0044] (6) 100 g of thermoplastic polyolefin CA10A, 50 g of first polypropylene NS06, 30 g of second polypropylene K8003, 20 g of hydrogenated styrene-isoprene copolymer 4052, 70 g of magnesium hydroxide, 0.5 g of anti-copper agent MD1024, 15 g of functional titanium dioxide IR-1000, 15 g of modified nano far-infrared ceramic powder, 15 g of modified rutile titanium dioxide, 3 g of hexachlorocyclotriphosphazene hindered phenol, and 0.5 g of hindered Amine light stabilizer C2020 was added to a high-speed mixer and mixed for 10 minutes at a speed of 100 r / min. Then it was added to a twin-screw extruder. The temperatures of each screw zone were 200°C, 205°C, 210°C, 215°C, 218°C, and 220°C. The head temperature was 220°C, the screw speed was 500 r / min, and it was melt-plasticized. After cooling and shaping by a three-roll calender, an infrared heat reflective thermoplastic polyolefin waterproof membrane was obtained. Embodiment 3

[0045] (1) Under a nitrogen atmosphere, 3.5 g of hexachlorocyclotriphosphazene and 2.1 g of 4,5-diaminobenzene-1,2-diphenol were added to a flask containing toluene solvent and stirred to disperse. Then, 6.6 g of triethylamine was added thereto and stirred to mix evenly. The temperature was controlled at 100°C and the reaction was carried out for 6 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed and dried to obtain an intermediate product 1.

[0046] (2) Under a nitrogen atmosphere, 5.5 g of the intermediate product 1 and 6.6 g of triethylamine were added to chloroform and stirred for dispersion. At 15° C., 22 g of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl chloride was added thereto. The temperature was raised to 55° C. and the reaction was carried out for 12 h. After the reaction was completed, the mixture was rotary evaporated, washed with saturated brine, and dried to obtain hexachlorocyclotriphosphazene hindered phenol.

[0047] (3) 4 g of calcium hydride was added to chloroform solvent, and the mixture was stirred at room temperature for 20 min. Then, 14 g of aminopropyltriethoxysilane and 3.3 g of formaldehyde were added thereto, and the mixture was stirred and reacted at 50°C for 40 min. Then, 5.5 g of intermediate 1 was added thereto, and the mixture was heated to 60°C and reacted under nitrogen protection for 5 h. After the reaction, the mixture was filtered, rotary evaporated, washed, and dried to obtain hexachlorocyclotriphosphazene silane.

[0048] (4) Add 0.2 g of hexachlorocyclotriphosphazene silane to a 75% by mass ethanol aqueous solution, stir and disperse, then add 20 g of dry nano far-infrared ceramic powder, ultrasonically disperse for 20 min, heat to 65 °C, and continue to react for 40 min. After the reaction is completed, dry and grind to obtain modified nano far-infrared ceramic powder.

[0049] (5) Add 20 g of rutile titanium dioxide to deionized water, adjust the pH to 6 with 10% by mass hydrochloric acid, add 0.3 g of hexachlorocyclotriphosphazene silane, stir and disperse for 20 min, heat to 75 °C, react for 2 h, and after the reaction is completed, centrifuge, wash with deionized water, dry, and grind to obtain modified rutile titanium dioxide.

[0050] (6) 100g thermoplastic polyolefin CA10A, 20g first polypropylene NS06, 50g second polypropylene K8003, 40g hydrogenated styrene-isoprene copolymer 4052, 70g magnesium hydroxide, 1g anti-copper agent MD1024, 20g functional titanium dioxide IR-1000, 20g modified nano far-infrared ceramic powder, 20g modified rutile titanium dioxide, 4g hexachlorocyclotriphosphazene hindered phenol, 2g hindered amine photocatalyst Stabilizer C2020 was added to a high-speed mixer and mixed for 10 minutes at a speed of 100 r / min. Then it was added to a twin-screw extruder. The temperatures of each screw zone were 200°C, 205°C, 210°C, 215°C, 218°C, and 220°C, the head temperature was 220°C, the screw speed was 400 r / min, and it was melt-plasticized and cooled and shaped by a three-roll calender to obtain an infrared heat reflective thermoplastic polyolefin waterproof membrane. Embodiment 4

[0051] (1) Under a nitrogen atmosphere, 3.5 g of hexachlorocyclotriphosphazene and 2 g of 4,5-diaminobenzene-1,2-diphenol were added to a flask containing toluene solvent and stirred to disperse. Then, 6.6 g of triethylamine was added thereto and stirred to mix evenly. The temperature was controlled at 100°C and the reaction was carried out for 7 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed and dried to obtain an intermediate product 1.

[0052] (2) Under a nitrogen atmosphere, 5.5 g of the intermediate product 1 and 8.8 g of triethylamine were added to chloroform and stirred for dispersion. At 10° C., 18 g of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl chloride was added thereto. The temperature was raised to 60° C. and the reaction was carried out for 10 h. After the reaction was completed, the mixture was rotary evaporated, washed with saturated brine, and dried to obtain hexachlorocyclotriphosphazene hindered phenol.

[0053] (3) Add 5.5 g of calcium hydride to chloroform solvent, stir at room temperature for 30 min, then add 15.4 g of aminopropyltriethoxysilane and 5 g of formaldehyde, stir and react at 50°C for 60 min, add 5.5 g of intermediate 1, raise the temperature to 60°C, react for 7 h under nitrogen protection, filter, rotary evaporate, wash and dry to obtain hexachlorocyclotriphosphazene silane.

[0054] (4) Add 0.3 g of hexachlorocyclotriphosphazene silane to a 75% by mass ethanol aqueous solution, stir and disperse, then add 20 g of dry nano far-infrared ceramic powder, ultrasonically disperse for 15 min, heat to 65 °C, and continue to react for 40 min. After the reaction is completed, dry and grind to obtain modified nano far-infrared ceramic powder.

[0055] (5) 20 g of rutile titanium dioxide was added to deionized water, and the pH value was adjusted to 6 using 10% by mass hydrochloric acid. 0.3 g of hexachlorocyclotriphosphazene silane was added thereto, and the mixture was stirred and dispersed for 25 min. The mixture was heated to 85 °C and reacted for 2 h. After the reaction was completed, the mixture was centrifuged, washed with deionized water, dried, and ground to obtain modified rutile titanium dioxide.

[0056] (6) 100g thermoplastic polyolefin CA10A, 50g first polypropylene NS06, 30g second polypropylene K8003, 30g hydrogenated styrene-isoprene copolymer 4052, 60g magnesium hydroxide, 0.8g anti-copper agent MD1024, 25g functional titanium dioxide IR-1000, 25g modified nano far-infrared ceramic powder, 25g modified rutile titanium dioxide, 5g hexachlorocyclotriphosphazene hindered phenol, 0.1g The hindered amine light stabilizer C2020 was added to a high-speed mixer and mixed for 5 minutes at a speed of 100 r / min. Then it was added to a twin-screw extruder. The temperatures of each screw zone were 200°C, 205°C, 210°C, 215°C, 218°C, and 220°C, the head temperature was 220°C, the screw speed was 400 r / min, and it was melt-plasticized. After cooling and shaping by a three-roll calender, an infrared heat reflective thermoplastic polyolefin waterproof membrane was obtained. Embodiment 5

[0057] (1) Under a nitrogen atmosphere, 3.5 g of hexachlorocyclotriphosphazene and 2 g of 4,5-diaminobenzene-1,2-diphenol were added to a flask containing toluene solvent and stirred to disperse. Then, 7 g of triethylamine was added thereto and stirred to mix evenly. The temperature was controlled at 105°C and the reaction was carried out for 8 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed and dried to obtain an intermediate product 1.

[0058] (2) Under a nitrogen atmosphere, 5.5 g of the intermediate product 1 and 8.8 g of triethylamine were added to chloroform and stirred for dispersion. Then, 17.6 g of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl chloride was added thereto at 20°C. The temperature was raised to 55°C and the reaction was carried out for 16 h. After the reaction was completed, the mixture was rotary evaporated, washed with saturated brine, and dried to obtain hexachlorocyclotriphosphazene hindered phenol.

[0059] (3) Add 3.85 g of calcium hydride to chloroform solvent, stir at room temperature for 25 min, then add 13.2 g of aminopropyltriethoxysilane and 5.5 g of formaldehyde, stir and react at 55 °C for 50 min, add 5.5 g of intermediate 1, raise the temperature to 65 °C, react for 6 h under nitrogen protection, filter, rotary evaporate, wash and dry to obtain hexachlorocyclotriphosphazene silane.

[0060] (4) Add 0.3 g of hexachlorocyclotriphosphazene silane to a 75% by mass ethanol aqueous solution, stir and disperse, then add 20 g of dry nano far-infrared ceramic powder, ultrasonically disperse for 20 min, heat to 65 °C, and continue to react for 40 min. After the reaction is completed, dry and grind to obtain modified nano far-infrared ceramic powder.

[0061] (5) Add 20 g of rutile titanium dioxide to deionized water, adjust the pH to 6 with 10% by mass hydrochloric acid, add 0.4 g of hexachlorocyclotriphosphazene silane, stir and disperse for 30 min, heat to 85 °C, react for 1 h, and after the reaction is completed, centrifuge, wash with deionized water, dry, and grind to obtain modified rutile titanium dioxide.

[0062] (6) 100g thermoplastic polyolefin CA10A, 40g first polypropylene NS06, 20g second polypropylene K8003, 30g hydrogenated styrene-isoprene copolymer 4052, 90g magnesium hydroxide, 0.1g anti-copper agent MD1024, 30g functional titanium dioxide IR-1000, 30g modified nano far-infrared ceramic powder, 30g modified rutile titanium dioxide, 5g hexachlorocyclotriphosphazene hindered phenol, 1.5g The hindered amine light stabilizer C2020 was added to a high-speed mixer and mixed for 5 minutes at a speed of 100 r / min. Then it was added to a twin-screw extruder. The temperatures of each screw zone were 200°C, 205°C, 210°C, 215°C, 218°C, and 220°C, the head temperature was 220°C, the screw speed was 500 r / min, and it was melt-plasticized. After cooling and shaping by a three-roll calender, an infrared heat reflective thermoplastic polyolefin waterproof membrane was obtained.

[0063] Comparative Example 1

[0064] The difference between this comparative example and Example 1 is that step (6) does not contain hexachlorocyclotriphosphazene hindered phenol.

[0065] Comparative Example 2

[0066] The difference between this comparative example and Example 1 is that step (6) does not contain modified nano far-infrared ceramic powder.

[0067] Comparative Example 3

[0068] The difference between this comparative example and Example 1 is that step (6) does not contain modified rutile titanium dioxide.

[0069] Refer to GB27789-2011 to test the mechanical properties of waterproof membrane.

[0070] Table 1:

[0071]

[0072] It can be seen from the table that the thermoplastic polyolefin waterproof membrane prepared by the present invention has good mechanical properties.

[0073] The heat aging performance was tested according to ASTM D6878. The test conditions were heat aging in an oven at 135°C for 56 days. The tensile strength retention rate (%) = tensile strength after aging / tensile strength before aging.

[0074] Use the thermal insulation film tester to test the thermal insulation rate.

[0075] Refer to ASTM C1371-15 to test solar reflectance.

[0076] Table 2:

[0077]

[0078] It can be seen from the above table that the thermoplastic polyolefin waterproof membrane prepared by the present invention has excellent heat aging resistance.

[0079] Refer to GB 8624-2012 to test the flame retardant properties of waterproof membrane.

[0080] Table 3:

[0081]

[0082] It can be seen from the table that the waterproof coiled materials prepared by the present invention all have good flame retardant properties.

[0083] The artificial climate accelerated aging test was carried out with reference to GB 27789-2011, and the aging time was 10000h.

[0084] Table 4:

[0085]

[0086] It can be seen from the table that the waterproof roll material prepared by the present invention has good weather resistance.

[0087] exist Figure 2In the NMR carbon spectrum, three groups of peaks appear in the low-field region, corresponding to the three groups of carbon signals on the benzene ring, among which the peak at the chemical shift of 145.8 ppm is the aromatic carbon signal connected to N (C-1), the peak at the chemical shift of 144.1 ppm is the aromatic carbon signal connected to O (C-3), and the peak at the chemical shift of 119.5 ppm is the aromatic carbon signal that is not connected to either (C-2); the peak at the chemical shift of 75.9 ppm in the mid-field region is the methylene carbon signal connected to both O and N atoms (C-5), and the peak at the chemical shift of 59.1 ppm corresponds to the methylene carbon signal connected to the siloxy group in the structure (C-9); the two groups of peaks at the chemical shifts of 54.6 and 45.6 ppm are the two methylene carbon signals connected to the N atom (C-4, 6); the high peak at the chemical shift of 16.0 ppm in the high-field region is the terminal methyl carbon signal peak (C-10).

[0088] The above embodiments are explanations of the present invention; however, the present invention is not limited to the specific details in the above embodiments, and various equivalent substitutions or simple modifications made by those skilled in the art within the technical concept of the present invention should all fall within the protection scope of the present invention.

Claims

1. An infrared heat reflective thermoplastic polyolefin waterproofing membrane, characterized in that: The waterproof coiled material is composed of the following components in parts by weight: 100 parts by weight of thermoplastic polyolefin, 20-50 parts of a first polypropylene, 10-30 parts of a second polypropylene, 5-20 parts of a hydrogenated styrene-isoprene copolymer, 60-90 parts of magnesium hydroxide, 10-30 parts of functional titanium dioxide IR-1000, 10-30 parts of modified nano far-infrared ceramic powder, 10-30 parts of modified rutile titanium dioxide, 2-5 parts of hexachlorocyclotriphosphazene hindered phenol, 0.1-2 parts of hindered amine light stabilizer C2020, and 0.1-1 parts of anti-copper agent MD1024; The preparation method of the modified nano far-infrared ceramic is: (1) Under a nitrogen atmosphere, hexachlorocyclotriphosphazene and 4,5-diaminobenzene-1,2-diphenol were added to a flask containing a toluene solvent, stirred and dispersed, and triethylamine was added thereto, stirred and mixed evenly, and the temperature was controlled at 100-110°C, and the reaction was carried out for 5-8 hours. After the reaction was completed, the reaction was cooled to room temperature, filtered, washed, and dried to obtain an intermediate product 1, whose structural formula is: ; (2) Add calcium hydride to chloroform solvent, stir at room temperature for 20-30 minutes, then add aminopropyltriethoxysilane and formaldehyde, stir and react at 50-55°C for 40-60 minutes, add intermediate 1, raise the temperature to 60-65°C, react for 5-7 hours under nitrogen protection, filter, rotary evaporate, wash and dry to obtain hexachlorocyclotriphosphazene silane; (3) adding hexachlorocyclotriphosphazene silane to a 75% by mass ethanol aqueous solution, stirring and dispersing, and then adding dry nano far-infrared ceramic powder thereto, ultrasonically dispersing for 10-20 minutes, heating to 60-70° C., and continuing the reaction for 20-40 minutes. After the reaction is completed, drying and grinding are performed to obtain modified nano far-infrared ceramic powder; The preparation method of the modified rutile titanium dioxide is: Add rutile titanium dioxide to deionized water, adjust the pH to 6 with 10% hydrochloric acid, add hexachlorocyclotriphosphazene silane, stir and disperse for 20-30 minutes, heat to 75-85°C, react for 1-2 hours, centrifuge after the reaction, wash with deionized water, dry, and grind to obtain modified rutile titanium dioxide; The preparation method of the hexachlorocyclotriphosphazene hindered phenol is as follows: Under a nitrogen atmosphere, the intermediate product 1 and triethylamine are added to chloroform, stirred and dispersed, and β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl chloride is added thereto at 10-20°C, the temperature is raised to 55-60°C, and the reaction is carried out for 10-16 hours. After the reaction is completed, the reaction is rotary evaporated, washed with saturated brine, and dried to obtain hexachlorocyclotriphosphazene hindered phenol.

2. An infrared heat reflective thermoplastic polyolefin waterproofing membrane as claimed in claim 1, characterized in that: The method comprises the following steps: Thermoplastic polyolefin, the first polypropylene, the second polypropylene, hydrogenated styrene-isoprene copolymer, magnesium hydroxide, anti-copper agent, functional titanium dioxide IR-1000, modified nano far-infrared ceramic powder, modified rutile titanium dioxide, hexachlorocyclotriphosphazene hindered phenol, and hindered amine light stabilizer are added to a high-speed mixer, mixed at a speed of 100 r / min for 5-10 minutes, and then added to a twin-screw extruder, melt-plasticized, and cooled and shaped by a three-roll calender to obtain an infrared heat reflective thermoplastic polyolefin waterproof membrane.

3. The infrared heat reflective thermoplastic polyolefin waterproof membrane according to claim 1, characterized in that: In the above (1), the mass ratio of hexachlorocyclotriphosphazene, 4,5-diaminobenzene-1,2-diphenol and triethylamine is 1:0.4-0.6:1.8-2.

4. The infrared heat reflective thermoplastic polyolefin waterproofing membrane according to claim 1, characterized in that: In the above (2), the mass ratio of calcium hydride, aminopropyltriethoxysilane, formaldehyde and intermediate product 1 is 0.7-1:2.4-2.8:0.6-1:

1.

5. The infrared heat reflective thermoplastic polyolefin waterproof membrane according to claim 1, characterized in that: In the above (3), the mass of hexachlorocyclotriphosphazene silane is 10-20% of the mass of the nano far-infrared ceramic powder.

6. The infrared heat reflective thermoplastic polyolefin waterproofing membrane according to claim 1, characterized in that: The mass of the hexachlorocyclotriphosphazene silane is 10-20% of the mass of rutile titanium dioxide.

7. The infrared heat reflective thermoplastic polyolefin waterproofing membrane according to claim 1, characterized in that: The mass ratio of the intermediate product 1, triethylamine and β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl chloride is 1:1.2-1.6:3.2-4.

8. The infrared heat reflective thermoplastic polyolefin waterproofing membrane according to claim 2, characterized in that: The temperatures of the screw zones are 200°C, 205°C, 210°C, 215°C, 218°C, and 220°C, the die temperature is 220°C, and the screw speed is 200-500r / min.

Citation Information

Patent Citations

  • High-flame-retardant long-service-life thermoplastic polyolefin waterproof coiled material and preparation method thereof

    CN117659882A

  • Preparation method and application of cyclotriphosphazene containing silicon functional groups

    CN102250147A

  • Naphthylamido cyclotriphosphazene based flame retardant and preparation method therefor

    CN104926882A